Ethnosciences Based Augmented Reality on Botanical Garden - Yunita Setiyaningsih; Rohman Dijaya; Suprianto Suprianto (JUITA : Jurnal Informatika, 2021)
Ethnosciences in natural knowledge needs to be developed as a learning material and insight. In the field of education, ethnoscience is not optimal if it is applied in theory or books. Along with the times, the theory of ethnoscience will be displaced by modern technology, therefore the means of knowledge need to be upgraded to more advanced media to gain new experiences, especially for future generations. Researchers are looking for an ethnoscience approach in the field of technology by taking samples of observations of plant species in the Botanical Gardens. The technology used to develop this media is Markerless Augmented Reality based on Android applications. Researchers use 3D plant model objects from plant species in functions for the environment, including: Waste particle absorbing plants; CO2-absorbing and O2-producing plants; Odor-absorbing/removing plants; Plants to deal with flooding; Absorbent/odor depressant plants; Plants to overcome inundation, Groundwater conservation plants; Beach safety and abrasion plants. The results of the implementation and testing of the application are built and run with the android.apk device. This application is called EARBot (Ethnoscience Based Augmented Reality on Botanical Garden) which is an educational application of knowledge about ethnoscience that uses Markerless Augmented Reality technology.